Drip Irrigation Efficiency Analysis and Crop Water Requirements of Mustard (Brassica juncea) in The Inceptisol Soil - Febrina Torop Simangunsong; Sumono Sumono; Ainun Rohana; Edi Susanto (Jurnal Rekayasa Pangan dan Pertanian, 2013)
Nowadays, the increasing human need for water, is in sharp contrast with the increasingly limited water availability, especially in agriculture so that adversely affect the crop production. Therefore it is necessary to use the availability of water effectively and efficiently by creating an appropriate irrigation technologies and efficient in water as drip irrigation. This study was aimed to analyze the efficiency of drip irrigation and crop water requirements of mustard using inceptisol soil. The measurements were made by direct observation in the field at three growth phases, namely the initial, middle, and late phases. The results showed that the crop water requirements of mustard in the early phase was 2.88 mm.day-1, in the middle phase was 6.58 mm.day-1 and in the late phase of growth was 6.1 mm.day-1. Efficiency consumption produced was very high with average of 100% and storage efficiency was low i.e < 90%. This indicated an imbalance between water usage efficiency and storage, so that the production of mustard plant that produced was not optimal. Key words: efficiency, drip irrigation, inceptisol soil, crop water requirement, mustard